0
$$\frac{\partial u}{\partial x}(x,y)=f(x,y,u(x,y))$$
$$\frac{\partial u}{\partial y}(x,y)=g(x,y,u(x,y))$$
$$u(x_0,y_0)=u_0$$

I want to write this but as an equation, I have tried

\begin{equation}
& =\frac{\partial u}{\partial x}(x,y)=f(x,y,u(x,y))\\
& =\frac{\partial u}{\partial y}(x,y)=g(x,y,u(x,y))\\
u(x_0,y_0)=u_0
\end{equation}

but can't get it to work.

Any feedback would be greatly appreciated

  • 1. Don't use $$; use \[ \] instead. 2. You can not use & inside an equation; use align instead of equation. Then \frac{\partial u}{\partial x}(x,y) &= f(x,y,u(x,y))\\ . – Sigur Jan 2 '15 at 14:16
  • Ok thanks, but how do I get each statement onto individual lines, but for the entire equation to be marked as one equation. – Sam Houston Jan 2 '15 at 14:17
  • 2
    Use aligned inside equation then. See: tex.stackexchange.com/a/171473/14757 – Sigur Jan 2 '15 at 14:19
2

Is this what you want:

\documentclass{scrreprt}
\usepackage{amsmath}
\begin{document}
 %(xyz) as a placeholder
 \begin{alignat}{2}
  (xyz) &= \frac{\partial u}{\partial x}(x,y) &&=f(x,y,u(x,y))\\
  (xyz) &= \frac{\partial u}{\partial y}(x,y) &&=g(x,y,u(x,y))\\
  (xyz) &= u(x_0,y_0) &&=u_0
\end{alignat}
\end{document}

enter image description here

  • Thanks for your answer, very close, just I wanted them all to be called one equation though. Ive worked out how to do it from Singur's comment above – Sam Houston Jan 2 '15 at 14:28
  • 2
    The space after equal sign is wrong since the correct use is &=. – Sigur Jan 2 '15 at 14:54
  • yes, i edited it... – user69453 Jan 2 '15 at 15:57
  • will you also post a new image to go with the modified code? – Mico Jan 2 '15 at 15:59
  • everything edited! – user69453 Jan 2 '15 at 16:11

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.